Dichelyne (Cucullanellus) bodiani n. sp. and Cucullanus hansoni Olsen, 1952 (Nematoda: Cucullanidae) from fishes off New Caledonia - Moravec, František; Justine, Jean-Lou (Systematic parasitology, 2019)
Two species of cucullanid nematodes collected from the intestine of marine fishes off New Caledonia were studied with the use of light and scanning electron microscopy (SEM): Dichelyne (Cucullanellus) bodiani n. sp. from Bodianus perditio (Quoy & Gaimard) (Perciformes: Labridae), characterised mainly by the small size of the body (males and gravid females 2.26-3.13 mm and 2.46-3.32 mm long, respectively), the presence of very long spicules (1.53-1.66 mm in length), the remarkably large seminal vesicle and the arrangement of caudal papillae, is the second known species of Dichelyne Jägerskiöld, 1902 parasitising fishes of the Labridae and the second nominal species of this genus recorded from fishes in New Caledonian waters. Cucullanus hansoni Olsen, 1952, originally described from Hawaii, is now, after 67 years, again reported from its type-host, Sufflamen fraenatum (Latreille) (Tetraodontiformes: Balistidae), from off New Caledonia. The SEM examination of C. hansoni, used in this species for the first time, revealed some new morphological details, such as the presence of a median precloacal cuticular elevation or the shape of deirids and distal tips of spicules, as well as the exact location of caudal papillae and phasmids in the male. This is the seventh species of Cucullanus Müller, 1777 recorded from fishes off New Caledonia.
Keywords: Ascaridoidea; Species Specificity; Nová Kaledonie; Female; New Caledonia; Animals; ženské pohlaví; mužské pohlaví; druhová specificita; Male; zvířata; Ascaridida; Perciformes